Arms trafficking - Zgaga, Sabina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2015)
The provision of arms for the commission of crimes is one of the typical forms of aiding and abetting. This article discusses arms trafficking as a form of aiding and abetting the commission of core crimes. It opens with a discussion of aiding and abetting as a form of complicity in the Rome Statute and the case law of the International Criminal Court. Furthermore, the article also analyses the regulation of legal arms trafficking in international and European law. Accordingly, the international criminal law further regulates illegal arms trafficking as an international crime and as complicity to core crimes. Therefore, the article first presents arms trafficking as an international crime and subsequently discusses arms trafficking as complicity in core crimes. The article concludes with a discussion on the regulation of arms trafficking in Slovene law, beginning with legal arms trafficking according to the Firearms Act-1 and ending with illegal arms trafficking as a crime.
Keywords: mednarodni kriminal; organizirani kriminal; trgovina z orožjem